Vulnerable Creation: Vulnerable Human Life between Risk and Tragedy1 - Springhart, Heike (Dialog, 2017)
In this paper a theology of vulnerability is explored by describing three bridges between risk and tragedy. Conceptually, ontological and situational vulnerability will be explored as the basis of anthropological realism. Hermeneutically, a case study is done by interpreting the documentary film “Roadside Radiation,” which shows attempts to live a normal life in tragedy in the “death zone” around Chernobyl. The theological bridge unfolds a theological approach to vulnerability that grasps its processive character.